Controlling the Size and Magnetic Properties of Nano Cofe2o4 by Microwave Assisted Co-Precipitation Method - Casagrande-Denardin, J (IOP PUBLISHING LTD, 2018)
In this report, cobalt ferrite nanoparticles synthesized using microwave assisted co-precipitation method was reported. Efforts have been made to control the particles size, distribution, morphology and magnetic properties of cobalt ferrite nanoparticles by varying the concentration of NaOH solution and microwave irradiation time. It was observed that the rate of nucleation and crystal growth was influenced by the tuning parameters. In that way, the average crystallite size of single phase cobalt ferrite nanoparticles was controlled within 9-11 and 10-12 nm with an increase of base concentration and microwave irradiation time, respectively. A narrow size distribution of nearly spherical nanoparticles was achieved through the present procedure. A soft ferromagnetism at room temperature with the considerable saturation magnetization of 58.4 emu g(-1) and coercivity of 262.7 Oe was obtained for the cobalt ferrites synthesized with 2.25 M of NaOH solution for 3 and 7 min of microwave irradiation time, respectively. The cobalt ferrite nanoparticles synthesized with a shorter reaction time of 3-7 min was found to be advantageous over other methods that involved conventional heating procedures and longer reaction time to achieve the better magnetic properties for the technological applications.